2013
DOI: 10.1108/gm-01-2013-0004
|View full text |Cite
|
Sign up to set email alerts
|

Women's leadership as narrative practice

Abstract: PurposeThe paper discusses the “narrative practices” utilised by women leading in a small sample of Early Years services in the North East of England. These Early Years settings are presented as an alternative site for studying women's experiences of leadership. It examines the way in which these women use narrative strategies and approaches to work in collaborative, community based services for young children and their families.Design/methodology/approachThe study is drawn from a larger study into narratives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 51 publications
(61 reference statements)
0
3
1
Order By: Relevance
“…Authors like Uzkurt et al (2013) asserted that organizations with innovative workforce have been found more goal oriented; thereby investigating the role of organizational innovation is important. A significant and direct relationship is found between organizational innovation and achieving organizational goal (Ha & Lo, 2018); Hurley and Choudhary (2016); (Irfan & Marzuki, 2018); Powell (2012); Robson (2013); (Uddin et al, 2013;Uzkurt et al, 2013). Contrary to previous studies, the current study extends the body of knowledge and outlined organizational innovation as moderating variable between achieving strategic goal and organizational productivity (Manu, 1992;Narver, Slater, & MacLachlan, 2004;Noble, Sinha, & Kumar, 2002;Siguaw, Simpson, & Enz, 2006).…”
Section: Organizational Innovationcontrasting
confidence: 54%
See 2 more Smart Citations
“…Authors like Uzkurt et al (2013) asserted that organizations with innovative workforce have been found more goal oriented; thereby investigating the role of organizational innovation is important. A significant and direct relationship is found between organizational innovation and achieving organizational goal (Ha & Lo, 2018); Hurley and Choudhary (2016); (Irfan & Marzuki, 2018); Powell (2012); Robson (2013); (Uddin et al, 2013;Uzkurt et al, 2013). Contrary to previous studies, the current study extends the body of knowledge and outlined organizational innovation as moderating variable between achieving strategic goal and organizational productivity (Manu, 1992;Narver, Slater, & MacLachlan, 2004;Noble, Sinha, & Kumar, 2002;Siguaw, Simpson, & Enz, 2006).…”
Section: Organizational Innovationcontrasting
confidence: 54%
“…Succession planning activities includes comprehensive strategic plan that employee adopt and later apply to solve critical problem which ultimately help organizations to achieve firm goals (Kiumarsi, Isa, Jayaraman, Amran, & Hashemi, 2020;Seniwoliba, 2015). The use of staffing plan drives efficient workforce which impart values in achieving sustainable goals of the organizations (Aslam, Aslam, Ali, & Habib, 2013;Hurley & Choudhary, 2016;Omidi & Shafiee, 2018;Powell, 2012;Robson, 2013). The job analysis and design process provide autonomy, variety and task significance to employee in order to achieve firm performance (Belias & Sklikas, 2013;Tufail, Bashir, & Shoukat, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, we outline a novel approach to leadership coaching that was underpinned by a belief that transformational leaders need not, in fact probably should not, enact leadership through individual acts whether those acts are loud or soft (Wood, 2017). Instead, actions should evolve as an adaptive response to the practice context (Male and Palaiologou, 2015), focusing on the social and relational processes that support trajectory (not outcome) of individuals and institutions (Robson, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Shift is seen in the emphasis on the relational construct of leadership in ECE which is seen as a social and shared process (Dunlop, 2008;Thornton, 2006). Robson (2013) employs the term "leadership as practice" to emphasise more about where, how and why leadership work is being organised and accomplished than is about who is offering visions for others to do the work" (p. 4). According to Schomberg (2008), ECE leadership is complex, partly due to the diversity of programmes for children.…”
Section: Leadership In Ecementioning
confidence: 99%